2012
DOI: 10.1371/journal.pone.0051044
|View full text |Cite
|
Sign up to set email alerts
|

Arresten, a Collagen-Derived Angiogenesis Inhibitor, Suppresses Invasion of Squamous Cell Carcinoma

Abstract: The turnover of extracellular matrix liberates various cryptic molecules with novel biological activity. Among these are the collagen-derived anti-angiogenic fragments, some of which are suggested to affect carcinoma cells also directly. Arresten is an endogenous angiogenesis inhibitor that is derived from the non-collagenous domain of the basement membrane collagen IV α1 chain. As the mere prevention of tumor angiogenesis leads to hypoxia that can result in selection of more aggressive cell types and reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 54 publications
3
32
0
Order By: Relevance
“…Interestingly, down-regulation of Lipocalin2 (LCN2), a marker for kidney injury (Viau et al, 2010), implicated in kidney epithelial cell morphogenesis (Gwira et al, 2005) and previously shown to be dysregulated in Apc Min/+ intestinal adenomas (Reichling et al, 2005), was observed in the APC shRNA MDCK cells. Other dysregulated genes including the alpha 1 subunit of type IV collagen (COL4A1, a basement membrane component), C-X-C chemokine receptor type 7 (CXCR7), and ADAM metallopeptidase with thrombospondin type 1, motif 6 (ADAMTS6), are implicated in controlling cell-cell or cell-matrix interactions (Kuhn, 1995; Bevitt et al, 2005; Hou et al, 2010; Aikio et al, 2012). These data collectively support a model in which APC loss-of-function in epithelial cells (through mutation and deletion of its c-terminus or gene silencing) leads to loss of polarity and tissue architecture, and subsequent tumor initiation, via altered communication between neighboring cells and the substratum.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, down-regulation of Lipocalin2 (LCN2), a marker for kidney injury (Viau et al, 2010), implicated in kidney epithelial cell morphogenesis (Gwira et al, 2005) and previously shown to be dysregulated in Apc Min/+ intestinal adenomas (Reichling et al, 2005), was observed in the APC shRNA MDCK cells. Other dysregulated genes including the alpha 1 subunit of type IV collagen (COL4A1, a basement membrane component), C-X-C chemokine receptor type 7 (CXCR7), and ADAM metallopeptidase with thrombospondin type 1, motif 6 (ADAMTS6), are implicated in controlling cell-cell or cell-matrix interactions (Kuhn, 1995; Bevitt et al, 2005; Hou et al, 2010; Aikio et al, 2012). These data collectively support a model in which APC loss-of-function in epithelial cells (through mutation and deletion of its c-terminus or gene silencing) leads to loss of polarity and tissue architecture, and subsequent tumor initiation, via altered communication between neighboring cells and the substratum.…”
Section: Resultsmentioning
confidence: 99%
“…The non-collagenous domain of type IV collagen α1 also contains a 26-kDa fragment known as arresten that, once cleaved becomes an endogenous angiogenesis inhibitor shown to also efficiently inhibit proliferation, migration and invasion of a highly metastatic human tongue SCC cell line (Aikio, Alahuhta et al 2012). Arresten is also known to inhibit the proliferation, migration and tube formation of different types of endothelial cells through α1β1 integrin receptors (Nyberg, Xie et al 2008).…”
Section: Proteasesmentioning
confidence: 99%
“…The binding affinity state of many integrins can be regulated at the cell surface by several stimuli, allowing regulation of the intensity of adhesion during cellular interactions and migration 39 . Several reports have shown that integrin 1 1 in particular is associated with migration and invasion of cancer cells 40,41 . In this study, SCC-4 cells in which integrin 1 mRNA was strongly expressed showed high migration and invasion abilities.…”
Section: Discussionmentioning
confidence: 99%